The Effect of Implementation of Syam-OK Based Online Learning Policies and Lecturer Competence on Student Learning Motivation at the Faculty of Social Sciences and Law, Makassar State University - Nina Agustina; Muhammad Guntur; Risma Niswaty (Jurnal Ilmiah Ilmu Administrasi Publik, 2023)
This study aims to examine the Effect of Implementation of Syam-Ok-Based Online Learning Policies and Lecturer Competence on Student Learning Motivation in the Faculty of Social Sciences and Law, Makassar State University. This type of research is a quantitative research using a descriptive approach. Data collection techniques were carried out by means of observation, interviews, questionnaires and documentation. The data analysis technique used consists of testing the validity and reliability of the instrument, descriptive statistical analysis, normality test and inferential statistical analysis. The results of the study show that the implementation of the Syam-Ok-based online learning policy is well implemented with a percentage of 75.73%, the competence of lecturers at the Faculty of Social Sciences and Law, Makassar State University is in the good category with a percentage of 79.20%, student learning motivation is in the good category with a percentage of 73%, the implementation of online learning policies based on Sham-Ok has a significant influence on student learning motivation with a percentage of influence of 56.9% in the medium category, lecturer competence has a significant influence on student learning motivation with a percentage of influence of 70.2% in the high category , and the implementation of Syam-Ok-based online learning policies and lecturer competencies together can influence student learning motivation in the Faculty of Social Sciences and Law, Makassar State University with an influence percentage of 70.4% in the high category and 29.6% influenced by other variables. Keywords: Policy Implementation, Lecturer Competence and Motivation